Studi Kasus Asuhan Keperawatan pada Pasien Post Sectio Caesarea dengan Masalah Menyusui Tidak Efektif melalui Intervensi Pijat Oksitosin - Nurhidayah Dewi Pramesthi; Dwi Sri Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Cesarean section is a surgical procedure that often causes delayed breast milk production due to postoperative pain, anesthesia effects, limited mobilization, and disruption of oxytocin hormone stimulation. This condition can lead to ineffective breastfeeding in postpartum mothers. One non-pharmacological intervention that can be performed to help facilitate breast milk production is oxytocin massage. This study aims to describe the application of oxytocin massage on the smoothness of breast milk production in post-cesarean section patients with indications of oligohydramnios. The research method used a descriptive design with a case study approach on Mrs. D P1A0 post-cesarean section in the Kalibiru Lor Room of Wates Regional Hospital, Kulon Progo, Yogyakarta. The intervention was conducted for 3x24 hours through oxytocin massage, breastfeeding education, warm compresses, family support, and observation of breast milk production. The results showed that before the intervention, the patient reported that her breast milk had not flowed smoothly and she felt less confident about breastfeeding. After performing oxytocin massage for 3x24 hours, the patient reported that her breast milk began to flow more smoothly, her breasts felt more comfortable, and she appeared more confident in breastfeeding. Additionally, there was a reduction in pain from a scale of 6 to 2 and an improvement in the patient's mobilization ability. Oxytocin massage is effective in helping to improve the smoothness of breast milk production and can be used as a non-pharmacological nursing intervention for post-cesarean section patients.